The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0309364611409617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of joint alignment and type on mechanical properties of thermoplastic articulated ankle-foot orthosis

Abstract: Background: Articulated or hinged ankle-foot orthosis (AFO) allow more range of motion. However, quantitative investigation on articulated AFO is still sparse. Objective: The objective of the study was to quantitatively investigate effects of alignment and joint types on mechanical properties of the thermoplastic articulated AFO. Study design: Tamarack dorsiflexion assist flexure joints with three durometers (75, 85 and 95) and free motion joint were tested. The AFO joint was aligned with the center of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Thus, the AFO was classified as an articulated AFO with adjustable plantarflexion resistive moment. The resistive moment of the AFO was measured under 4 different spring conditions (S1, S2, S3 and S4) with a custom automated device used in an earlier study (Gao et al, 2011). The S1 was a baseline condition where no steel spring was installed on the AFO, and it represented an AFO with a minimum resistive moment.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the AFO was classified as an articulated AFO with adjustable plantarflexion resistive moment. The resistive moment of the AFO was measured under 4 different spring conditions (S1, S2, S3 and S4) with a custom automated device used in an earlier study (Gao et al, 2011). The S1 was a baseline condition where no steel spring was installed on the AFO, and it represented an AFO with a minimum resistive moment.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely due the ankle generated greater power to overcome the greater resistance of prefabricated AFO. The lesser range of motion and higher power generation in prefabricated AFO condition might be attributed to the greater resistance offered by the pre-fabricated AFO due to misalignment as Gao et al 6 reported that stiffness of articulated ankle joint increases with misalignment. Other than joint alignment, the shank upright of the custom AFO was bigger than the pre-fabricated AFO, which might also be one of the reasons behind the difference of kinematics and kinetics in two AFO conditions.…”
Section: -11mentioning
confidence: 99%
“…As the axes of anatomical joints are partially specified by the skeletal structure, it is difficult to infer only from external observations. Gao et al 6 reported that optimal alignment of ankle joint provides minimal ankle stiffness, while posterior and anterior alignment provide significantly higher stiffness. Fatone and Hansen 7 described that ankle joint misalignment can cause significant calf band movement which might injure the skin.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the static balancing points where the effect of gravity can be cancelled out by both the human and passive spring torques, shown in Equation 9.…”
Section: Formulationmentioning
confidence: 99%
“…Variations between subjects' dynamic parameters such as mass and inertia are often compensated actively, while skeletal alignment is often performed manually by sliding rigid segments to specific discrete lock points. Misalignment between the joint centre of the person and the assistive device can result in joint damage, and is particularly problematic in children where bone growth is rapid and the damage due to misalignment is more pronounced [28,9]. Assistance is often afforded to every joint uniformly, potentially resulting in muscle atrophy and bone loss due to lack of exertion.…”
Section: Introductionmentioning
confidence: 99%